(untitled) (International Journal of Engineering and Computer Science, 2017)
Optical Character recognition which is the original method of character recognition many times gives poor recognition rate due to error in character segmentation. Segmentation is a very important task in every OCR system. OCR system separates the scanned handwritten image text documents into lines, words and characters. The accuracy of OCR system mainly depends on segmentation algorithm and noise removal technique being used. Segmentation of handwritten Devnagari text is difficult when compared with printed Devnagari or printed English or any other printed document, because of its structural complexity and increased character set. It contains vowels, consonants and half form consonant. This system addresses the segmentation of handwritten Devnagari text document, the most popular script of Indian sub – continent into lines, words and characters. Mainly artificial neural network technique is used to design to pre-process, segment and recognize Devnagari characters.